Global diversity of two widespread, colony‐forming diatoms of the marine plankton, Chaetoceros socialis (syn. C. radians) and Chaetoceros gelidus sp. nov. Issue 6 (8th November 2013) - Chamnansinp, Atchaneey; Li, Yang; Lundholm, Nina; Moestrup, Øjvind; Bowler, C.
<x xml:space="preserve">Abstract</x> Marine phytoplankton samples containing diatoms of the Chaetoceros socialis group were collected from Thailand, China, Denmark, and Greenland, and cells were isolated into culture for light and electron microscopy and DNA sequencing of D1–D3 of the LSU rDNA. Species of this lineage are characterized by three short and one long setae extending from each cell, the long setae from several cells joining into a common center to form large colonies, which are sometimes visible with the naked eye. Phylogenetic analyses including sequences from other parts of the world revealed segregation into three groups. Most sequences fell into two large clades, one comprising material from cold waters, whereas the other contained material from warmer waters. Strain CCMP 172 from the Strait of Georgia, Washington State, USA, formed a separate group. The warm‐water species included Chinese and Thai material and therefore probably also material from the type locality of C. socialis, Hong Kong. It is characterized by all setae being covered by spines and the setae extending from the valve at some distance from the margin. In the resting spores, both valves are ornamented with spines. The cold‐water material is characterized by three spiny and one mostly smooth long setae, and the setae extend from the valve near the margin. Both valves of the resting spore are smooth. This material is described as C. gelidus sp. nov. C. radians, described from the Baltic in 1894, is considered a synonym of C. socialis. CCMP172 is in many ways intermediate and probably constitutes a separate species. The published evidence on this globally distributed and sometimes bloom‐forming group of species indicates higher species diversity than presently thought.